(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Neolithic pre pottery people in Syria were interested in the shape of the house. It was circular and quadrilateral, and decorated the elements of the house from inside (the earth and the walls). The decorations were either geometrical confined only to the walls or animal themes that included the earth and the walls, Taurus was their main theme . However, the embodiment of man was confined to women on the floor of the house. These works reflected the artistic level of the man of that era associated with the dogmatic side.